Oratory: Its development and influence - Long, Olive A. (My University, 1898)
Introduction: Among the traits which distinguish man from lower organized life that of conveying that by means of articulates speech stands foremost. Scientists cannot say with certainty that lower animals do not have an action of the brain corresponding to that. But all scientific investigation has failed to prove that animals of lower order have an articulate language. Man, alone is gifted with this mighty power. From the earliest historic time, we find man influencing man by means of speech. Although physically strength and valor were valuable requisites of political power a cunning brain and ready tongue were no less important factors. Tradition, antedating history, though enveloped in a haze of mystery, brings to us records of eloquence and oratory, although rough as the monuments which mark the simple grandeur of primitive that were doubtless far more potent in forming their simple political relations than any efforts of modern time.
Citation: Long, Olive A. Oratory: Its development and influence. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Man; Scientists; History; Articulate Language; Theses; Manuscripts (documents)